Governing maritime space: The South China Sea as a Mediterranean cultural area - Hans-Dieter Evers (University of Bonn, Center for Development Research (ZEF), 2014)
Whereas many institutions are in place to govern urban and rural land, maritime areas are less well covered. This situation of a "governance void" has led to uncertainty and conflicts. Thus the South China Sea has become a contested maritime space. In this paper the cultural theory of Oswald Spengler will be applied to stress the importance of conceptions of space as a basis for maritime governance. By comparing it to other maritime spaces, like the Baltic and the Mediterranean Sea, lessons will be drawn from the "longue durée" of history, as analysed by French historian Fernand Braudel. Embedded in this larger theoretical framework special attention will be placed on the Malay and Javanese Nusantara conception of maritime space and its implication for governing the South China Sea.
Keywords: 330; South China Sea; maritime space; mediterranean seas; cultural analysis; connectivity